Justification of design and parameters of Bernoulli–vacuum gripping device. (16th November 2017) - Savkiv, Volodymyr; Mykhailyshyn, Roman; Duchon, Frantisek; Fendo, Olena
The dynamics of the air flow between interacting surfaces of Bernoulli–vacuum gripping device and object of manipulation is analysed. The methods of increasing lifting capacity in given devices are presented. The equation for defining pressure distribution in between interacting surfaces of gripping device and object of manipulation and equations for calculation of power characteristics is calculated. The results of theoretical researches of Bernoulli–vacuum gripping devices with different forms of active surfaces are introduced.